Clinical Results of Acute ST Elevation Myocardial Infarction Patients with the Fast Tract Management System in Naresuan University Hospital - Thamaree and Ampai Tangsirirat, Khanittha Lairakdomrong, Suthasinee (Naresuan University Journal: Science and Technology (NUJST); Vol 24 No 3 (2016): September - December 2016, 2016)
Background: Acute ST-elevation myocardial infarction (STEMI) is a life-threatening emergency cardiovascular condition. Mortality is still high in rural region. Objective: to identify mortality rate and evaluate the clinical outcomes of acute STEMI patients using the fast tract management system at Naresuan University Hospital (NUH) Material and Method: Descriptive review of clinical parameters from STEMI patients who participated in the fast tract management system Results: Between Jan 2010 to Sep 2013 , 191 STEMI patients were enrolled. The 147 patients (77%) were referrals and 44 patients (23%) were non-referrals. They were predominantly male patients with an average age of 65 years. The risk factors of coronary artery disease (CAD) were dyslipidemia (86.9%), hypertension (61.3%), smoking (51.3%) and diabetes mellitus (18.3%). Cardiac arrest was found in 16.2% and 14.1% presented with cardiogenic shock. 86.4% received reperfusion therapy with 37.2% got primary percutaneous coronary intervention (PCI). The median door to balloon time and door to needle time for non-referral patients were 89 and 58 minutes, respectively. The median time to treatment was 226 min in the thrombolytic group and 234 min in the primary PCI group. The overall mortality rate was 11.5% which was much lower than the previous data of NUH (33.3%). For the referred patients, the median first medical contact (FMC) to device time was 344 min. Mortality rate of primary PCI in referral group (17.9%) was higher than in non-referral group (6.3%). Conclusion: The mortality rate at NUH is lower than before having established fast tract management system but still high as compare to standard of care. Fibrinolytic therapy is preferred for the treatment of choice at non-PCI capable hospital and PCI will be considered for failed fibrinolysis or presence of contraindication to fibrinolysis. Shortening of pain to treatment time by fast tract management system is the mainstay to improve survival in the patients who suffer from STEMI.   Keywords: ST elevation myocardial infarction, fast tract
Keywords: ST elevation myocardial infarction, fast tract